A possible precursor prior to the Lushan earthquake from GPS observations in the southern Longmenshan - Wang, Qixin (Sci Rep, 2020)
Global Positioning System (GPS) stations installed in and around the epicenter of the Lushan earthquake (Mw 6.7), which occurred almost 5 years after the 2008 Wenchuan earthquake, recorded preseismic deformation corresponding to the Lushan earthquake within the southern Longmenshan thrust belt. A half-space dislocation model is used to simulate the theoretical values of the postseismic displacements caused by the 2008 Wenchuan earthquake, and after transforming the reference frame and filtering the GPS displacement time series, the theoretical and observed GPS values are compared to identify the geodetic anomaly preceding the Lushan earthquake. The abnormal extent of this geodetic anomaly decreases with increasing epicentral distance for each GPS site. This geodetic signal reflects preslip along a locked section of the 2013 seismogenic fault, which caused the accumulation of elastic strain energy until the faulting strength was overcome, thereby generating the Lushan earthquake. Hence, this anomaly might be used as an observable and identifiable precursor to forecast an impending earthquake within a period of less than two and half years before its occurrence.